Evolution of the constitutional position of selected German-speaking countries’ heads of state in the 20th/21st century - Łukaszewski, Marcin (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2014)
This paper is an attempt to show the evolution of the constitutional position of the head of state in the years 1920–2013 in Austria, Liechtenstein and Switzerland, with special reference to the specificity of these systems (Austrian federalism, Liechtenstein’s strong position of the monarch and collegial head of state in the Swiss case). It is based on a comparative analysis of the constitutional provisions of constitutional acts and their corresponding amendments. The timeframe of the paper is based on the period 1920–2013, due to the fact that at the very beginning of the 1920s two of the constitutional acts were created in the countries which are the subject of the paper: Austria (1920) and Liechtenstein (1921), which, despite many changes, exist today. The aim of the paper is to indicate differences in the position of the political head of state in 1920, and almost a century later.

Przedmiotem artykułu jest próba ukazania ewolucji ustrojowej pozycji głowy państwa w latach 1920–2013 w Austrii, Liechtensteinie i Szwajcarii, ze szczególnym uwzględnieniem specyfiki tych systemów politycznych (austriackiego federalizmu, silnej pozycji księcia w Liechtensteinie i kolegialnej głowy państwa w Szwajcarii). Artykuł został oparty na analizie komparatystycznej zapisów konstytucyjnych z uwzględnieniem odpowiednich nowelizacji. Ramy czasowe artykułu zostały oparte na okresie 1920–2013 w związku z tym, że początek lat 20. jest związany z powstawaniem konstytucji dwóch z trzech państw stanowiących przedmiot analizy: Austrii (1920) i Liechtensteinu (1921), które to akty prawne, pomimo wielu zmian, funkcjonują do dzisiaj. Celem artykułu jest wskazanie różnic w pozycji ustrojowej głowy państwa w 1920 roku i prawie 100 lat później.
Ewolucja konstytucyjnej pozycji głowy państwa w wybranych państwach niemieckojęzycznych na przełomie XX i XXI wieku
Keywords: Austria; Liechtenstein; Switzerland; head of state; constitutional position; Liechtenstein; Szwajcaria; głowa państwa; pozycja ustrojowa